2013
DOI: 10.5751/es-05822-180413
|View full text |Cite
|
Sign up to set email alerts
|

Local Perceptions of Climate Variability and Change in Tropical Forests of Papua, Indonesia

Abstract: ABSTRACT. People everywhere experience changes and events that impact their lives. Knowing how they perceive, react, and adapt to climatic changes and events is helpful in developing strategies to support adaptation to climate change. Mamberamo in Papua, Indonesia, is a sparsely populated watershed of 7.8 million hectares possessing rich tropical forests. Our study compares scientific and traditional ecological knowledge (TEK) on climate, and analyzes how local people in Mamberamo perceive and react to climati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 44 publications
1
58
0
Order By: Relevance
“…Padmanaba et al (2012) describe the process of participatory land planning. Boissière et al (2013) describe our assessment of community views regarding climate variability.…”
Section: Approach and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Padmanaba et al (2012) describe the process of participatory land planning. Boissière et al (2013) describe our assessment of community views regarding climate variability.…”
Section: Approach and Methodsmentioning
confidence: 99%
“…Many researchers, including ourselves, have noted the environmental trends recognized by local people without necessarily considering the function, scope, and operational details of how this recognition is achieved (e.g., Hellier et al 1999, Lund et al 2010, Basuki et al 2011, Boissière et al 2013, Danielsen et al 2014a, 2014b. Active oversight is implicit in work on traditional resource management (Berkes et al 1998) and in the context of collaborative or participatory monitoring ).…”
Section: Introductionmentioning
confidence: 99%
“…However, two case studies concluded that women assigned a higher value or WTP to this ecosystem service (Calvet-Mir et al, 2016;Vivithkeyoonvong and Jourdain, 2017). Boissiere et al (2013) showed that women and men might focus on different types of regulatory services. Men had a greater perception of the potential benefits that tropical forests can have on mitigating drought frequency, while women were more perceptive of their benefits for the mitigation of flood frequency.…”
Section: Regulatingmentioning
confidence: 99%
“…As in other systems in which social and political changes may have more pressing impacts on local livelihoods and grassland ecosystems than the direct effects of climate change (Boillat and Berkes 2013, Boissière et al 2013, Thébault et al 2014, the environmental changes occurring in Tibet also have an explicitly political dimension. Due to the combined pressures of restrictive grazing policies, declining rangeland health, and growing local populations, people report having more problems with grassland management than in the past, which produces conflicts and leads them to seek out village leaders to resolve both environmental and interpersonal issues.…”
Section: Political Dimensions Of Global Change Knowledge and Actionmentioning
confidence: 99%